ANALISIS FAKTOR-FAKTOR PENGHAMBAT PEMASARAN PRODUK TABUNGAN HAJI (STUDI KASUS PADA BANK SUMUT SYARIAH MEDAN) - Irmawati Irmawati; Amsari Syahrul (Jurnal El Rayyan: Jurnal Perbankan Syariah, 2022)
The purpose of the study was to find out how the promotion carried out by the SUMUT Syariah bank so that customers had hajj savings. to find out how the services provided by the SUMUT Syariah bank are so that customers have Hajj savings. This research uses a qualitative approach. The results showed that in order to introduce Hajj iB Makbul savings to the wider community, the steps used by Bank Sumut Syariah KCP Marelan Raya were similar to policies carried out by other banks. The difference is, the North Sumatran bank focuses on the problem of advertising plans. In this case, Bank Sumut Syariah itself runs advertising using television, radio, newspapers, magazines and internet advertisements. The bank also provides leaflets that we arrange on the customer slip table, customer service desk, and teller. The bank also introduces Hajj savings to companies and schools that have a relationship with Bank Sumut Syariah and markets Bank Sumut Syariah products, including the Hajj iB Makbul savings product. Which is by utilizing marketing decision making which intends to persuade and maintain customer loyalty. Some of the problems faced by Bank Sumut Syariah Medan in running or offering Hajj iB Makbul savings are the lack of knowledge or understanding of the community about Islamic banks, lack of experienced human resources, especially in the marketing section and inadequate facilities such as the lack of ATM machines. The forms of Hajj Savings Services at Bank Sumut Syariah Medan are: First serve wholeheartedly and fulfill customer expectations so that customers become loyal, second offer quality products, third present accurate and correct data and information, and fourth prioritize company interests over personal interests and work units.